STRATEGI PENGEMBANGAN USAHATANI JAMBU KRISTAL (Studi Kasus : Pusat Pelatihan Pertanian Dan Pedesaan Swadaya Wira Tani Di Desa Tegal Sawah, Karawang Timur, Karawang) - Rizka Kharisma; Abubakar Abubakar; Luthfi Nur’azkiya (Universitas Galuh, 2023)
Crytal guava is family of guava that many people like. Karawang Regency is one Training of the areas that produce cyrstal guava in West Java Province. Rural and Agriculture Training Center Wira Tani Karawang is one of the non government organization that implementing crystal guava farming in East Karawang District. Crystal guava farming has the potential to be developed, but there are still constraints on internal and external factors. This research aims a : 1) Formulate alternative strategies and 2) Determine strategic priorities in the development of crystal guava cultivation at P4S Wira Tani Karawang. The research method used is analytical descriptive. The location selection was done intentionally (purposive). The sample used in this research consisted of 12 respondents. The analytical method used is SWOT and QSPM matrix. The result of SWOT and QSPM matrix analysis show: 1) There are 9 formulations of alternative strategies that can be applied in P4S Wira Tani Karawang and 2) Priority strategy in this research is optimizing the use of superior seeds with a score of 9,32